THE COVID-19 PANDEMIC: A CASE STUDY OF DISASTER RESPONSE AT UNIVERSITAS KRISTEN DUTA WACANA - Atmadi, Lenggana Relung; Vanadian, Heppi; Kushadiwijaya, RM Silvester Haripurnomo (Faculty of Medicine Universitas Kristen Duta Wacana, 2024)
Introduction: This study examined the disaster response system of Universitas Kristen Duta Wacana (UKDW) during the COVID-19 pandemic. As a complex institution with interconnected components, UKDW plays a vital role in disaster mitigation and response. Method: Using a qualitative research approach, this study analyzed data from focus group discussions, in-depth interviews, and questionnaires to assess university preparedness and response to the pandemic. Result: The findings revealed that UKDW's response to COVID-19 involved several key stages: pandemic identification, mitigation and preparedness, changes in learning strategies, and evaluation. While the university demonstrated adaptability and resilience, challenges, such as communication gaps and resource limitations, were identified. Conclusion: The study's recommendations include strengthening disaster response training, improving communication channels, and enhancing collaboration with external partners to enhance UKDW's preparedness for future crises.